Dynamics of Indian fresh mango export - BALYAN, KAVITA; KUMAR, SHIV; CHAHAL, V P; KUMAR, SANDEEP (The Indian Journal of Agricultural Sciences, 2015)
Increasing integration of global markets after WTO has brought several changes in fresh mango export. The sustainability of exporters' income depends on acceptance of consignments by the importing countries who have established legally vetted system of safe import of food commodities. To adjust to these changes, the Indian system of export controls faltered to meet the standards of overseas markets. Adherence to safe export norms is sine qua non to have credible sustainable export. Visualizing the need to discern and quantify the direction of fresh mango export, time series data spanning from 1990-2012 was analysed. From the analysis, it can be concluded that domestic supply of mango is mainly driven by expansion of area rather than productivity. High standards of SPS measures of importing countries raised cost of compliance of safe export norms for which Indian exporters faced problems to adjust to these standards. These challenges need to overcome through generation of research based scientific knowledge for structuring food safety norms and policy alignment according to the changing global regulations. Policy options for streamlining diversified export are to encourage food testing laboratories to get accreditation from international agencies setting up world class food testing and inception infrastructure particularly in clusters with significant presence of exporters to encourage importing countries to set up office for certification of export consignments, and to strengthen prerequisite physical resources for safe export of fresh mango.